An Effective Model Predictive Control Method With Self-Balanced Capacitor Voltages for Single-Phase Three-Level Shunt Active Filters - Komurcugil, Hasan; Bayhan, Sertac; Guler, Naki; Blaabjerg, Frede (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
This paper presents an effective model predictive control (MPC) method for single-phase three-level T-type inverter-based shunt active power filters (SAPFs). The SAPF using T-type inverter topology has not been reported in the literature yet. Contrary to most of the existing MPC methods, the proposed MPC method eliminates the need for using weighting factor and additional constraints required for balancing dc capacitor voltages in the cost function. The design of cost function is based on the energy function. Since the factor used in the formulation of the energy function does not have any adverse influence on the performance of the system, the cost function becomes weighting factor free. The weighting factor free based MPC brings simplicity in the practical implementation. The effectiveness of the proposed MPC method has been investigated in steady-state as well as dynamic transients caused by load changes. The theoretical considerations are verified through experimental studies performed on a 3 kVA system.
Keywords: Inverters; Predictive control; Capacitors; Switches; Voltage control; Active filters; Power harmonic filters; Shunt active power filter; model predictive control; energy function